Peningkatan Penguasaan Membaca Permulaan Melalui Metode Struktural Analitik Sintetik Pada Siswa Kelas I Sekolah Dasar - Najwassyifa; Tasrif, Arrahim; Sugiharti, Rini Endah (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study aims to enhance the mastery of early reading skills among Grade I students at SDN Galudra through the implementation of the SAS method. Employing a Classroom Action Research (CAR) approach with both quantitative and qualitative methods, this research seeks to improve the quality of learning. The findings reveal substantial improvements in students' early reading skills, as evidenced by the percentage of students achieving mastery in reading skills, which increased from 33% to 73% and ultimately reached 100% after two cycles. These results demonstrate the efficacy of utilizing the SAS method as a strategy to improve basic reading skills in Grade I students.